Determinasi Komitmen Organisasi: Peran Pelatihan, Kompetensi, dan Kepuasan Kerja di Sekretariat Daerah Kabupaten Jembrana - Santika, i putu santika; Nugraha, Surya; Budiasa, I Ketut (Value : Journal of Management and Business, 2026)
This research examines how training and competence influence organizational commitment, with job satisfaction acting as an intervening variable at the Regional Secretariat of Jembrana Regency. Human resource management has an important role in enhancing organizational performance, especially within public institutions. Training programs and competency development are viewed as key strategies for improving employees’ abilities, attitudes, and motivation at work, which can subsequently affect their level of job satisfaction and commitment to the organization. The study employed a quantitative method using a causal research design. The population included all 152 employees working at the Regional Secretariat of Jembrana Regency. From this population, 60 respondents were selected through a probability sampling technique. Data collection was conducted using questionnaires, and the data were analyzed through path analysis. The findings indicate that both training and competence positively and significantly affect job satisfaction. In addition, training, competence, and job satisfaction also show a significant influence on organizational commitment. Nevertheless, job satisfaction does not function as a full mediator in the relationship between training, competence, and organizational commitment. These results suggest that strengthening training programs and enhancing employee competencies are essential steps in increasing organizational commitment. Consequently, organizational leaders are encouraged to continuously improve the quality of training, develop employee competencies, and foster a supportive work environment in order to increase job satisfaction and strengthen commitment among employees.